Assessment of age‐specific safety of laparoscopic surgery in elderly patients with ovarian tumors. Issue 3 (2nd December 2015) - Otake, Akiko; Sasase, Aya; Suzuki, Atsuko; Takahashi, Kayo; Sasamoto, Naoko; Miyoshi, Yukari; Shioji, Mitsunori; Yamamoto, Yoshimitsu; Adachi, Kazushige
Abstract: Aim: We assessed the age‐specific safety of laparoscopic surgery in elderly patients with ovarian tumors. Material and Methods: We performed a retrospective analysis of 55 elderly patients treated by laparoscopic salpingo‐oophorectomy under the diagnosis of an ovarian tumor between January 2009 and December 2014. We divided patients into three groups: "young‐elderly" (aged 65–74), "old‐elderly" (aged 75–84), and "super‐elderly" (aged 85–105) and assessed clinical characteristics, surgical results and postoperative course. Statistical significance of categorical variables was examined by the Student's t ‐test, Mann–Whitney U test, or Fisher's exact test. Multiple regression analysis was used for multivariate analysis. Results: Of a total of 55 patients who underwent laparoscopic surgery, there were 36 patients in the young‐elderly group, 17 in the old‐elderly group, and two in the super‐elderly group. Statistical analysis was performed between the young‐elderly and the old‐elderly groups because of the small number in the super‐elderly group. More frequent comorbidities were found in the patients in the old‐elderly than in the young‐elderly group (Fisher's exact test, P = 0.007). There were no significant differences in operative time, estimated blood loss and postoperative hospital stay between the young‐elderly and old‐elderly groups. Intraoperative complications only occurred in the young‐elderly group. Postoperative complications occurred in all groups. Conclusions: Although patients in the old‐elderly group had a significantly higher risk for surgery, they had equivalent surgical results to the young‐elderly group for laparoscopic salpingo‐oophorectomy.